Alcohol consumption and pre-drinking in Australian undergraduates - Caudwell, Kimberley Mitchell (Curtin University, 2017)
This thesis reports research on the application of psychological theory to predict, understand and change pre-drinking behaviour (i.e., consuming alcohol prior to attending a subsequent event). Three studies investigate the motivational and social-cognitive predictors of pre-drinking intentions and alcohol consumption. Two further studies based on these findings report the development and implementation of an online intervention to reduce pre-drinking alcohol consumption and related harm. Participants in the intervention reported reductions in these variables at follow-up.